Democratic Opposition Related Files
The series represents a highly variegated body of documents related to the activity of political opposition in Poland between 1976 and 1983. It records appeals, declarations, protests, open letters, interviews, reports, sermons, analyses and commentaries issued by or describing the activities of organized political groups, as well as the Polish Catholic Church and the representatives of various social groups including farmers, writers and academics. Worth singling out are the materials documenting the activity of: the Workers’ Defense Committee (KOR), the Movement for Human and Civil Rights (ROPCiO), the Student Solidarity Committee (SKS), the Society of Scientific Courses (TKN), the Polish Independence Agreement (PPN), the "Znak” Group, the Democratic Movement, Farmers’ Self Defense organizations; the Ósmego Dnia Theatre, the Believers’ Self-Defense Committee, the Free Trade Unions (WZZ), the Confederation of Independent Poland (KPN), NSZZ Solidarity, Rural Solidarity, the “Experience and Future” Group (DiP), the Independent Student Association (NZS), and the Independent Publishing House (NOWA). Apart from those mentioned above other documents worth mentioning include: individual testimonies of state repression, including files from court cases; leaked official documents publicized by the democratic opposition, including the classified censorship guidelines that served as the documentary basis of the Black Book of Censorship (New York: Vintage Books, 1984); and letters to Radio Free Europe regarding the image of the various dissident groups as disseminated by RFE. Accruals not expected